Condicionamento osmótico de sementes de melão - Nunes, Tenessee Andrade (2007)
The objective this work was verified the effect of osmocondition with polyethylem glycol 6000, nitrate of sodium and chloride of magnesium in germination and emergency of seedlings of melon. The experiments was carried in the laboratories belonging to the department of Vegetable Science of Universidade Federal Rural do Semi-Árido, Mossoró RN, during the months of August and September of 2006. It was utilized seeds of melon type Honey Dew variety Orange flesh. The experiment was divided in two rehearsals, the first was accomplished conditioning theseeds of melon in polyethylem glycol 6000 and the second being used the salts The osmocondition it was accomplished plastic boxes type gerbox. The demonstration consisted of seeds soaked only in distillation water. For soak in PEG 6000, it was utilized the potentials 0,00; -0,05; - 0,10 -0,20; -0,40; -0,60; -0,80 MPa. The second rehearsal also with soak, it was accomplished being used nitrate of sodium and and chloride of magnesium in concentrations of 1,0; 2,0; 3,0; 4,0; 5,0 e 6,0% in volume terms of solution. The boxes containing the seeds soaked they were placed in the stews incubator type BOD for 25ºC four 48 hours. The seeds were submitted to the standard test of germination and the development in the substrate among sand . The variables evaluated were: germination (normal seedlings, abnormal, firm and dead seeds), index of germination speed, height of seedlings, root length, mass matter dry of the whole seedlings. The experimental arrangement used for the first rehearsal was a completely randomized designs with seven treatments and four replications of 25 seeds. And for second rehearsal was a completely randomized design in factorial arrangement [(2 x 6) + 1] with four replications. It was verified effect significant for osmotic potentials for variables mass of dry of the whole seedlings, root length, abnormal seedlings, firm seeds and index of germination speed. The roots length of the seedlings of melon decreased with the increase of the osmotic potentials of polyethylem glycol 6000 in the solution of soak of the seeds. The index of germination speed increased with the increase of the potentials of polyethylem glycol in the solution of soak of the seeds. The osmoconditioning with PEG 6000 t showed germination of normal seedlings most larger to the control in all the appraised potentials. It was verified significant effect for theinteraction the factors type of salt x osmotic potentials for the variables root length and index ofgermination speed and firm seeds. The largest concentrations so much of chloride of magnesium as of nitrate of sodium they caused decrease in the length of root of the seedlings of melon. With the increase of the concentration of both salts in the solutions of soak of the seeds, it happened increase in the number of firm seeds. As at increased the saline concentration in the solutions of soak of the seeds, the index of germination speed decreased, that fall was more accentuated when it used the salt nitrate of sodium. The osmotic potential of -0,80 MPa induced of PEG 6000 eliminated the emergence of firm seeds of melon during the germination test. No have died seedsduring the conduce of rehearsal